2004
DOI: 10.1093/jn/134.10.2586
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Hemoglobin and Ferritin Concentrations Are Associated with Pregnancy Outcome in a Prospective Cohort of Chinese Women

Abstract: Prenatal anemia and iron deficiency are associated with adverse birth outcomes, but no previous studies have examined the relation between preconception anemia, iron deficiency, and pregnancy outcome in healthy women. We measured hemoglobin (Hb), ferritin, transferrin receptor (TfR), and vitamins B-6, B-12, and folate concentrations before pregnancy in 405 Chinese women (median time from sample collection to gestation end = 316 d). Both mild (95 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(120 citation statements)
references
References 35 publications
5
106
0
9
Order By: Relevance
“…The limitation is the change in eating habits of people depending on seasonal variances, which was disregarded in our study. As was shown in an earlier study (30), it may cause some oscillations in serum micronutrient levels.…”
Section: Discussionsupporting
confidence: 58%
“…The limitation is the change in eating habits of people depending on seasonal variances, which was disregarded in our study. As was shown in an earlier study (30), it may cause some oscillations in serum micronutrient levels.…”
Section: Discussionsupporting
confidence: 58%
“…However, substantial iron deficiency anemia (usually <80g/L) is associated with an increased incidence of LBW. The mechanism by which anemia could produce this effect is unknown, but other nutrient deficiencies are important contributing factors [10]. One study even reported harmful effects of iron supplementation [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have revealed an increased risk of low birth weight (7)(8)(9)12,36), preterm birth (7,8,36) and stillbirth (10,11) associated with anemia in pregnancy. The results of past studies greatly depend on the definition of anemia, the time when hemoglobin was measured and potential confounders used for adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…In China, low hemoglobin concentration was associated with increased risk for preterm birth, small-for-gestational-age foetuses and low birth weight (8). Women with anemia had infants who were at higher risk of having a low birth weight and foetal growth restrictions than infants born to non-anemic women (9). Anemia was also associated with a higher risk of stillbirth (10,11).…”
Section: Introductionmentioning
confidence: 99%